Waste Management Based On Waste To Energy Technology In Palopo City - Nur, Muh. Syainal; Husen, Achmad; Purwandari, Dian Alfia (CV. Literasi Indonesia, 2024)
The volume of waste in Indonesia especially in Palopo City increases every year, while the quality of waste management does not show good performance. The large population makes high consumption including energy needs, even though most of the national energy needs come from coal which is a source of pollutants. Waste to energy (WTE) is a modern waste management that utilizes waste into renewable energy, the conversion of waste into energy can be done with landfill gas (LFG) technology and incineration. The study aims to analyze the potential of waste management based on waste-to-energy technology in Palopo City. Quantitative descriptive research with observation and documentation instruments. To calculate the potential energy produced using LandGem-v302 and mathematical equations, to assess the feasibility of economic value using the criteria npv, irr, brc, and pp. The results of this study show that gas landfill technology has the potential to produce renewable energy. The results of the economic feasibility assessment of gas landfill technology meet all four criteria, thus the development of gas landfill technology can provide economic benefits. The results of incineration technology research have the potential to produce renewable energy. But from the results of the economic feasibility assessment unlike gas landfills, the combustion technology does not meet one of the economic value feasibility criteria. So the development of centration technology is not recommended to obtain economic benefits, the development of incineration technology is recommended to reduce waste.